2017
DOI: 10.1007/s12079-017-0411-9
|View full text |Cite
|
Sign up to set email alerts
|

Sulfatase-1 knockdown promotes in vitro and in vivo aggressive behavior of murine hepatocarcinoma Hca-P cells through up-regulation of mesothelin

Abstract: Our previous study (Oncotarget 2016; 7:46) demonstrated that the over-expression of sulfatase-1 in murine hepatocarcinoma Hca-F cell line (a murine HCC cell with lymph node metastatic [LNM] rate of >75%) downregulates mesothelin and leads to reduction in lymphatic metastasis, both in vitro and in vivo. In current work, we investigated the effects of Sulf-1 knockdown on mesothelin (Msln) and it's effects on the in vitro cell proliferation, migration, invasion, and in vivo tumor growth and LNM rate for Hca-P cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Moreover, Mahmoud et al made further exploration of SULF1 in HCC by constructing overexpressed and knockdown murine HCC cell lines. Their findings revealed that SULF1 could attenuate HCC cells EMT by downregulating mesothelin, thus inhibit cells growth and invasion in vitro and in vivo [127,128]. In contrast, SULF2 was reported to upregulate SNAI1 and vimentin to promote EMT in HCC [129].…”
Section: Sulfs Regulate Tumor Metastasis By Affecting Emt Processmentioning
confidence: 99%
“…Moreover, Mahmoud et al made further exploration of SULF1 in HCC by constructing overexpressed and knockdown murine HCC cell lines. Their findings revealed that SULF1 could attenuate HCC cells EMT by downregulating mesothelin, thus inhibit cells growth and invasion in vitro and in vivo [127,128]. In contrast, SULF2 was reported to upregulate SNAI1 and vimentin to promote EMT in HCC [129].…”
Section: Sulfs Regulate Tumor Metastasis By Affecting Emt Processmentioning
confidence: 99%